Performance analysis and tank test validation of a hybrid ocean wave-current energy converter with a single power takeoff. (15th November 2020) - Jiang, Boxi; Li, Xiaofan; Chen, Shuo; Xiong, Qiuchi; Chen, Bang-fuh; Parker, Robert G.; Zuo, Lei
Highlights: Design of a hybrid ocean wave-current energy converter with a single power take-off. Dynamic analysis and verification through water tank testing with co-existing wave and current inputs. Computational fluid dynamics analysis for turbine hydrodynamics. Power enhancement comparing to baseline tests of wave energy converter and turbine in isolation. Abstract: This paper introduces a hybrid ocean wave-current energy converter (HWCEC) that harvests energy from ocean waves and current simultaneously with a single power takeoff. The wave energy is extracted through relative heaving motion between a floating buoy and a submerged second body, while the current energy is extracted using a marine current turbine. Energy from both sources is integrated by a hybrid power takeoff whose concept is based on a mechanical motion rectifier. The hybrid power takeoff with two one-way clutches converts bidirectional, up-and-down motion from the waves into unidirectional rotation of the generator. Meanwhile a third one-way clutch couples the turbine with the same generator. The wave and current can simultaneously or separately drive the same generator through different engagement and disengagement statuses of the one-way clutches. Time-domain simulation is conducted with hydrodynamic coefficients obtained from computational fluid dynamics analysis and the boundary element method. Tank tests were conducted for an HWCEC under a co-existing wave and current inputs. For comparison, separate baseline tests of a turbine and a two-body point absorber, each acting in isolation, are conducted. Experimental results validate the dynamic modeling and show that an HWCEC can increase the output power with a range between 24 and 89% over either current turbine and wave energy converter acting individually, and it can reduce by up to 70% the peak-to-average power ratio compared with the wave energy converter on the tested conditions.